Computational analysis of magnetic effects on pulsatile flow of couple stress fluid through a bifurcated artery. (December 2016) - Srinivasacharya, D.; Rao, G. Madhava
Highlights: The blood flow through a bifurcated artery with couple stress fluid is investigated. Flow rate increased with an increase of all the parameters except for magnetic parameter. Impedance decreased with an increase of all parameters except for magnetic parameter. Shear stress is increasing with an increase in the values of couple stress fluid parameter. Shear stress decreased with increase of bifurcation angle along the inner wall of daughter artery. Abstract: Background and objectives: The objective of the present study is to investigate the magnetic field effect on pulsatile flow of blood through a bifurcated artery with mild stenosis in its parent lumen by taking blood as couple stress fluid. Methods: The equations governing the flow are made non-dimensional, and coordinate transformation is employed to convert the irregular boundary to a regular boundary. The resulting system of equations is solved numerically using the finite difference method. Results: The shear stress, flow rate and impedance near the apex with pertinent parameters are obtained numerically and analyzed graphically. Conclusions: It is noticed that physical quantities are changing suddenly with all parameters on both sides of the apex. This occurs because of back flow of the streaming blood at the onset of the lateral junction and secondary flow near the apex in the daughter artery.